2016
DOI: 10.1063/1.4966810
|View full text |Cite
|
Sign up to set email alerts
|

Effect of varying nitrogen flow rates on the optical properties of amorphous-SiCN thin films

Abstract: Series of amorphous silicon carbon nitride (a-SiCN) films are synthesized using RF-PECVD technique on glass and silicon substrates from precursor gas of silane, methane and nitrogen. In this work, the change in nitrogen flow rate from 0 sccm to 50 sccm is a mean used to vary the elemental composition and bonding properties which lead to change in optical properties. The films thickness varies between 327 nm to 944 nm. The changes for the stated properties are discussed against the change in the stated nitrogen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…Kozak et al [12] investigated the effect of the N 2 flow on the properties of Si-C-N amorphous thin films produced by magnetron sputtering. Rahmann et al [13] reported the effect of varying N 2 flow rates on the optical properties of amorphous-SiCN thin films.…”
Section: Introductionmentioning
confidence: 99%
“…Kozak et al [12] investigated the effect of the N 2 flow on the properties of Si-C-N amorphous thin films produced by magnetron sputtering. Rahmann et al [13] reported the effect of varying N 2 flow rates on the optical properties of amorphous-SiCN thin films.…”
Section: Introductionmentioning
confidence: 99%